2013
DOI: 10.1155/2013/514719
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract ofSolanum nigrumLeaves Induces Autophagy and Enhances Cytotoxicity of Cisplatin, Doxorubicin, Docetaxel, and 5-Fluorouracil in Human Colorectal Carcinoma Cells

Abstract: Colorectal cancer is a common cancer worldwide, and chemotherapy is a mainstream approach for advanced and recurrent cases. Development of effective complementary drugs could help improve tumor suppression efficiency and control adverse effects from chemotherapy. The aqueous extract of Solanum nigrum leaves (AE-SN) is an essential component in many traditional Chinese medicine formulas for treating cancer, but there is a lack of evidence verifying its tumor suppression efficacy in colorectal cancer. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 37 publications
5
56
0
1
Order By: Relevance
“…However, the exact mechanism is still unknown, the possible explanation is that some components of FZKA such as P. heterophylla, 32 A. membranaceus, 33 O. diffusa 34 and S. nigrum 35 have demonstrated anti-tumor activity in human tumor cells. In vitro study, we also found that the addition of FZKA and gefitinib to A549 (a cell line with low EGFR-TKI sensitivity) and H1650 (a cell line with EGFR-TKI resistance) cells resulted in down-regulation of p-EGFR and p-MAPK, suggesting the anti-proliferation effect on FZKA and gefitinib was acted through inhibiting the activation of EGFR and its downstream pathway Ras/Raf/MAPK (To be published).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact mechanism is still unknown, the possible explanation is that some components of FZKA such as P. heterophylla, 32 A. membranaceus, 33 O. diffusa 34 and S. nigrum 35 have demonstrated anti-tumor activity in human tumor cells. In vitro study, we also found that the addition of FZKA and gefitinib to A549 (a cell line with low EGFR-TKI sensitivity) and H1650 (a cell line with EGFR-TKI resistance) cells resulted in down-regulation of p-EGFR and p-MAPK, suggesting the anti-proliferation effect on FZKA and gefitinib was acted through inhibiting the activation of EGFR and its downstream pathway Ras/Raf/MAPK (To be published).…”
Section: Discussionmentioning
confidence: 99%
“…We aim to determine whether gefitinib plus CHM could prolong the progression-free survival (PFS) or median survival time (MST) in patients with NSCLC than gefitinib alone. Methods: We retrospectively analyzed 159 non-small-cell lung cancer patients with the method of retrospective case-control study, matching factors included gender, age categories (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79), pathological stage (IIIB or IV), smoking status (never: <100 lifetime cigarettes, or ever: ≥100 lifetime cigarettes), pathology, and performance status. Among the 159 patients, 100 patients treated with gefitinib (250 mg/day orally) plus CHM (''Fuzheng Kang'ai'' decoction, a Chinese herbal medicine, 250 ml/bid/day orally), 59 patients treated with gefitinib (250 mg/day orally) only.…”
mentioning
confidence: 99%
“…Since DLD-1 and HT-29 cell lines have TP53 mutations and are resistant to the TP53-mediated apoptosis, cell death might be induced in a CASP3-independent manner with the activation of autophagy. The inclusion of Solanum nigrum leaves in chemotherapeutic therapies has been suggested to improve the efficacy of CRC treatment 311 . Hence, rather than autophagy inhibition, activation of the autophagy pathway that leads to cell death is able to improve CRC treatment.…”
Section: Inhibitors and Activators Of Autophagy And The Upr In Crcmentioning
confidence: 99%
“…A randomized phase III trial showed that coadministration of temozolomide and interferon α2b (INF-α2b) increased the response rate from 13% to 24% and overall survival time from 8.4 to 9.7 months 53. Since various herbal water extracts have been reported to potentiate the therapeutic efficacy of chemotherapy drugs,25,26,5456 we evaluated whether the water extract of S. nigrum exhibits synergistic/additive effect with temozolomide against human MM A-375 cells. As illustrated in Figure 5, the cytotoxicity of the coadministered temozolomide and water extract of S. nigrum was increased statistically significantly to 97.0%±3.6% from 31.0%±7.5% for temozolomide ( P <0.01) and 55.0%±17.6% for the water extract of S. nigrum ( P =0.03), implicating synergistic effect was achieved between temozolomide and the water extract of S. nigrum against human MM A-375 cells.…”
Section: Resultsmentioning
confidence: 99%